Ḥaḍānah Anak dalam Keluarga Fatherless di Muara Batu (Aceh Utara): Kajian Sosiologis-Yuridis - Lizatul Amna (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This study aims to comprehensively examine the implementation of ḥaḍānah (child custody) in fatherless families in Muara Batu District, North Aceh Regency. The research focuses on identifying the underlying factors of fatherlessness, its psychological impacts on children and mothers, and its relevance to the principles of Islamic family law. The increasing number of children growing up without the presence of a father in the area reflects an imbalance in the post-divorce parental responsibilities, which has significant implications for the emotional and social well-being of children. This study employs a qualitative approach through in-depth interviews, field observations, and documentation with divorced mothers who hold custody rights, religious leaders, and local village officials across several villages in Muara Batu. The findings reveal that fatherlessness is primarily caused by economic constraints, emotional conflicts following divorce, the father’s remarriage, and low legal and religious awareness within the community. These conditions result in the absence of the father’s emotional and moral role model, while mothers experience heavy psychological and economic burdens as single caregivers. From the perspective of Islamic law, the practice of ḥaḍānah in this region has not yet fully reflected the principles of justice and shared responsibility as stipulated in the Compilation of Islamic Law (KHI). This study makes a unique contribution by integrating Islamic legal analysis with socio-psychological perspectives to understand fatherlessness within Aceh’s religious and cultural context. Therefore, the active involvement of religious institutions, legal counselors, and the Mahkamah Syar’iyah is essential to strengthen the implementation of ḥaḍānah that prioritizes the best interests of the child and ensures the father’s continued responsibility after divorce.